Marketing Approach In Islamic Donation Based-crowdfunding Platform In Malaysia: Exploratory Study - Wan Nur Fazni Wan Mohamad Nazarie; Nurul Aini Muhamed; Muhammad Iqmal Hisham Kamaruddin; Rafisah Mat Radzi; Aimi Fadzirul Kamarubahrin (Human Resource Management Academic Research Society, 2024)
Indexed by ERA